2007
DOI: 10.1007/s00441-007-0381-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental endocrine therapies promote epithelial cytodifferentiation and ciliogenesis in the gerbil female prostate

Abstract: The incidence of ciliated cells in the prostate gland of the female gerbil (Meriones unguiculatus) is uncommon and apparently becomes more frequent during androgen (testosterone cypionate) and anti-estrogen (letrozole) endocrine therapies. To evaluate the effects of such drug therapies on the induction of ciliogenesis in the glandular epithelium of female prostate glands, adult female gerbils aged 90 days were treated for 14 days with testosterone and letrozole after which their prostate glands were removed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
2
14
0
3
Order By: Relevance
“…Fibroblasts and smooth muscle cells (thick arrows); epithelial cell nuclei (arrows). (Brambell and Davis, 1940;Mahoney and Witschi, 1947;Shehata, 1972Shehata, , 1975Shehata, , 1980Gross and Didio, 1987;Satoh et al, 2001;Flamini et al, 2002;Santos et al, 2003Santos et al, , 2007. In the gerbil Meriones unguiculatus, the prostate is found in $ 80% of the animals , a proportion very similar to that in human females (Zaviacic, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts and smooth muscle cells (thick arrows); epithelial cell nuclei (arrows). (Brambell and Davis, 1940;Mahoney and Witschi, 1947;Shehata, 1972Shehata, , 1975Shehata, , 1980Gross and Didio, 1987;Satoh et al, 2001;Flamini et al, 2002;Santos et al, 2003Santos et al, , 2007. In the gerbil Meriones unguiculatus, the prostate is found in $ 80% of the animals , a proportion very similar to that in human females (Zaviacic, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The ten animals in the control group were injected subcutaneously with only vegetable oil. The animals of the other two groups were treated with sex steroid hormones dissolved in 0.05 ml of vegetable oil and injected every 48 hours for seven days (Santos et al, 2007). One group was injected subcutaneously 0.5 mg/kg of 17β-estradiol (Sigma) while another group, 0.5 mg/kg of testosterone cypionate.…”
Section: Hormone Treatmentmentioning
confidence: 99%
“…Sections of 4% paraformaldehyde-fixed female prostates were subjected to immunocytochemistry for the detection of androgen receptor (AR) and estrogen alpha receptor (ESR1), as described in protocols applied to the prostate [8,9,34]. Primary antibodies to AR (rabbit polyclonal IgG, N-20) and ESR1 (rabbit polyclonal IgG, MC-20) (Santa Cruz Biotechnology, Santa Cruz, CA) were employed at a dilution of 1:100 and 1:50, respectively.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…Testosterone treatment of adult gerbil female prostate [8,9] showed that this organ's epithelial and stromal cells express androgen receptors and that the hormonal stimulus causes secretory activity increase and dysplastic growth. Therefore, as it is a steroid-regulated gland, the changes in the hormonal serum levels can alter the female prostate structure and physiology.…”
Section: Introductionmentioning
confidence: 99%